Bacterial causes of upper & lower respiratory tract infection in Sheep: Jamal Salman Ali , Hayder Badri Abboud - Ali, Jamal Salman (The Iraqi Journal of Veterinary Medicine, 2005)
This study was designed to investigate the bacterial species that induceupper and lower respiratory tract infection in sheep, and to find out anyrelationship which may exist between them.Therefore two groups of sheep were employed. The first group wassuffering from certain respiratory signs. While the second group was apparentlyhealthy. Each group included 50 sheep. Research samples were collected for aperiod of six months from AL-Shulla Abattoir.Microbiological investigation indicated the isolation of certainmicroorganisms from all animals in both groups from nasal cavity, and from 34lungs of the first group and 16 lungs of the second group. The number of isolatesfrom the nasal cavity, were 200 from different species ,43 isolates from thebronchioles and 70 from the lungs tissue. On the other hand the number ofbacterial isolates from the nasal cavity, bronchioles and the lung tissue of thefirst group were 113, 29 and 55 respectively.The study revealed the isolation of potentially pathogenic bacteria from thelower respiratory system of both groups, these bacteria were namely Pasteurellahaemolytica of serotype (A2), Niesseria spp. and Corynebacterium pyogenes,the number of isolates were 6 for each, and 8 isolates of Staphylococcus aureus.These bacteria were also isolated from the nasal cavity. The isolation of thesebacteria from the nasal strongly suggested their presence in the lungs and theprobable role in lesion formation.Animal inoculation were performed to study the virulence of P.haemolytica which caused certain hemorrhagic lesion in the lung , liver andkidney, with areas of necrosis in the lungs of the experimentally inoculatedrabbit, and caused death in mice. While the inoculation of C. ovis caused thedeath of rabbits within 72 hours, together with the presence of multipleabscessation on the internal organs and abdomenal wall.Sensitivity tests indicated a high sensitivity of most isolates to Gentamicin,Erythromycin and Kanamycin.